Why Cadets And Officers Of Internal Affairs Of Uzbekistan Need English - Qarshiboyeva Z. Sh. (Euro Asian Journal Publishing, 2024)
This article provides information on how in today`s fast moving world it is of paramount importance to teach English in every educational institution of Internal Affairs in order to cooperate with international organizations, examine foreign experiences, bring up our legislation system to international level of standards and find new ways and methods of fighting against criminality
Keywords: foreign languages; English; cadets; officers